Gut microbiome alterations among Ghanaian children with asymptomatic malaria infections - Amma Aboagyewa Larbi; Moses Etsey; Obed Brew; Bismark Koduah; Rosemond Enam Mawuenyega; Emmanuel Kobla Atsu Amewu; Nehemiah Kweku Essilfie; Solomon Wireko; Alexander Kwarteng; Ben Adu Gyan (PLoS ONE, 2026)
The human gut microbiome, consisting of bacteria, archaea, fungi, and viruses, influences various physiological processes of the body. The gut microbiome composition is shaped by factors such as diet, geography, and antibiotic use. Malaria has been a global health challenge over the years, especially in low- and middle-income countries. This study investigated how asymptomatic malaria infection altered gut microbial communities in Ghanaian children, offering insights for novel malaria control strategies. Standard aseptic phlebotomy procedures were employed to collect venous blood samples for Plasmodium species detection. The gut microbial community was profiled by sequencing the 16S rRNA V4 region, and sequence data were processed using the DADA2 pipeline in R. Asymptomatic malaria infections were predominantly mixed with P. falciparum and P. malariae . Microbiome analysis revealed that Firmicutes and Bacteroidetes comprised nearly 70% of the total microbial population. Asymptomatic individuals showed a decrease in Firmicutes abundance from 52.5% to 44.0% and an increase in Bacteroidetes from 34.7% to 45.6%. There was also a slight increase in the abundance of Proteobacteria from 3.0% to 4.8%. At the genus level, Prevotella_9 was the most abundant and exhibited the highest variability in the infected groups. The Alloprevotella and Streptococcus genera increased in both infected groups, but Escherichia-Shigella was significantly elevated in only those with mixed infections. Faecalibacterium significantly declined in asymptomatic malaria-infected individuals compared to healthy controls, with variability further reduced in mixed infections. Beta-diversity analysis indicated a significant effect of malaria status on microbial composition (PERMANOVA, p < 0.05), explaining approximately 19.1% of the total variation captured by a 2D Principal Component Analysis (PCA) projection. These findings suggest a potential link between malaria infection and gut microbiota alterations and highlight microbial shifts associated with disease status.